How Organizational Field Networks Shape Interorganizational Tie-Formation Rates - Kenis, Patrick; Knoke, David (Academy of Management Review, 2002)
We investigate the impact of communication in field-level networks on rates of formation of interorganizational collaborative ties, such as strategic alliances and joint ventures. After developing the concept of an organizational field network (“field-net”), we derive a set of testable propositions and corollaries that relate field-net properties, such as density, reciprocity, centralization, multiplexity, and hierarchy, to subsequent nonlinear changes in interorganizational tie-formation rates. We conclude by discussing aspects of empirical research for testing the empirical validity of these propositions.